A retrospective study on prevalence, bacteriological profile and antibiotic sensitivity pattern of urinary tract infection in children of 2-12 years age in a tertiary care centre, Puducherry, India - Angamuthu, Dharmalingam; Bhaskar, Chandru; Aswathaman, Nalini (International Journal of Contemporary Pediatrics, 2019)
Background: Urinary tract infections (UTIs) are a common cause of acute bacterial illness in infants and children(1).Diagnosis is often missed in infants and children as urinary symptoms are minimal and nonspecific. It is becoming increasingly difficult to treat due to increasing prevalence of antimicrobial resistance among organisms. Method: It was done as a retrospective cross sectional study conducted on Children of 2-12 years of age suspected to have UTI from January 2018 to December 2018 in Pediatric Department of AVMCH. Results: Out of 286 children with symptoms suggestive of Urinary tract infection, 22(7.7%) were found to have culture positive UTI with 9.2% prevalence in 2-6 years age group as against 6.4% in 7-12 years of age group. Culture positive UTI was predominantly found in males in 2-6 years age group as against female predominance in 7-12 years age group. E. coli (45.5%) was the commonest organism isolated among them followed by Klebsiella. 90% of organisms were sensitive to Nitrofurantoin and 80% were sensitive to Amikacin(80%). Discussion: Culture positive UTI rate varies with gender and age group. It was predominantly found in males in 2-6 years age group as against female predominance in 7-12 years age group. E. coli and Klebsieella were the most common organisms with predominant sensitivity to Nitrofurantoin and Amikacin similar to other studies. Limitation of this study Retrospective study, small sample size and follow up for complications not done. Conclusion: This study concludes E. coli and Klebsieella were the most common organisms with predominant sensitivity to Nitrofurantoin and Amikacin. Antibiotics need to be selected based on organisms and their sensitivity pattern.